2018
DOI: 10.1021/acs.nanolett.8b03044
|View full text |Cite
|
Sign up to set email alerts
|

Clean Block Copolymer Microparticles from Supercritical CO2: Universal Templates for the Facile and Scalable Fabrication of Hierarchical Mesostructured Metal Oxides

Abstract: Metal oxide microparticles with well-defined internal mesostructures are promising materials for a variety of different applications, but practical routes to such materials that allow the constituent structural length scales to be precisely tuned have thus far been difficult to realize. Herein, we describe a novel platform methodology that utilizes self-assembled block copolymer (BCP) microparticles synthesized by dispersion polymerization in supercritical CO2 (scCO2) as universal structure directing agents fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 57 publications
0
25
0
Order By: Relevance
“…This is evidenced by the observation of efficient chain extension and formation of block copolymers. 13,19,36,52 Additionally, the swelling and sorption of PMMA lms with MMA has been studied extensively in scCO 2 . [53][54][55] As PMMA particles have a higher surface area than lms, they are even more likely to swell, with a K j estimated at 0.4 for MMA and 0.25 for CO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…This is evidenced by the observation of efficient chain extension and formation of block copolymers. 13,19,36,52 Additionally, the swelling and sorption of PMMA lms with MMA has been studied extensively in scCO 2 . [53][54][55] As PMMA particles have a higher surface area than lms, they are even more likely to swell, with a K j estimated at 0.4 for MMA and 0.25 for CO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The second low T g monomer was subsequently added using methodologies that have previously been reported in the literature. 27,32,42,44,45 The initial focus of this research was the synthesis of particles containing a PBzA phase (Table 3), as a model system. The conversion of BzA was calculated from the 1 H NMR spectrum by comparing the integral of the unreacted vinyl peak in the monomer (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…9,[17][18][19] We have recently shown that diblock copolymers of poly (methyl methacrylate) (PMMA) and P4VP can be used as templates to fabricate hierarchically structured metal oxides, in both a versatile and scalable manner. 20 Reversible additionfragmentation chain transfer (RAFT) controlled dispersion polymerisation in supercritical carbon dioxide (scCO 2 ) was used to synthesise nanostructured block copolymer microparticles. 21 The method yielded block copolymers with high blocking efficiencies and minimal block tapering, due to almost complete conversion of monomers at each stage of the polymerisation.…”
Section: Introductionmentioning
confidence: 99%
“…23 The resulting PMMA-b-P4VP microparticles were then used as sacrificial templates in the inorganic sol-gel synthesis of TiO 2 and LiFePO 4 with structural features on both the micro and nano-length scales. 20 However, our studies thus far have only focused on the use of simple AB-type diblock copolymers for application in structure directing. While it is well-established that AB copolymers predominantly form four distinct morphologies in the bulk (spheres, cylinders, bicontinuous gyroid and lamellar), addition of a third unique block has the potential to produce a wealth of additional nanostructures.…”
Section: Introductionmentioning
confidence: 99%